2015
DOI: 10.2220/biomedres.36.253
|View full text |Cite
|
Sign up to set email alerts
|

<b>Protein expression profile related to cisplatin resistance in bladder cancer cell lines detected by two-dimensional gel electrophor</b><b>esis </b>

Abstract: We used a proteomic approach to compare the differentially regulated protein expression profiles of cisplatin-naïve and cisplatin-resistant bladder cancer cell lines to screen candidate molecules related to cisplatin resistance. The cisplatin-resistant cell line T24 was established by the stepwise exposure of T24 cells to up to 40 μM of cisplatin. We performed a comprehensive study of protein expression in bladder cancer cell lines that included cisplatin-naïve (T24) and cisplatin-resistant cells (T24CDDPR) by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…These results were consistent with those from previous studies. Taoka et al (45) compared differential protein expression profiles between platinum-naïve and platinum-resistant bladder cancer cell lines to identify the candidate molecules associated with platinum resistance, and revealed that the expression of TKT was increased by 1.5-fold in platinum-resistant bladder cancer compared with that in platinum-naïve cells. Yang et al (31) also demonstrated that silencing of TKT significantly reduced cell viability and increased apoptosis in the presence of platinum via glutathione depletion and reactive oxygen species generation in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These results were consistent with those from previous studies. Taoka et al (45) compared differential protein expression profiles between platinum-naïve and platinum-resistant bladder cancer cell lines to identify the candidate molecules associated with platinum resistance, and revealed that the expression of TKT was increased by 1.5-fold in platinum-resistant bladder cancer compared with that in platinum-naïve cells. Yang et al (31) also demonstrated that silencing of TKT significantly reduced cell viability and increased apoptosis in the presence of platinum via glutathione depletion and reactive oxygen species generation in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we noted that the most significantly enriched GO terms and KEGG pathways for genes encoding proteins in the network were related to metabolic dysfunction, suggesting that aberrations in metabolism may play an important role in OS metastasis and recurrence. Previous research has reported that PCK2 downregulation leads to a reduction in energy metabolism and may subsequently decrease susceptibility to chemotherapeutic drugs 53. This may explain why low expression of PCK2 is associated with increased likelihoods of metastasis and recurrence in OS patients.…”
Section: Discussionmentioning
confidence: 93%
“…Conversely, another study reported that overexpression of PCK2 hindered tumorigenesis and slowed the growth of tumor-repopulating cells growth 52. Moreover, expression of the PCK2 protein gradually decreased in cisplatin-resistant bladder cancer cells compared to levels in cisplatin-naïve cells, and this decrease was dependent on the cisplatin concentration 53.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, T24 cells resistant to cisplatin (40 μM) (T24CDDPR) were established and compared with cisplatin-naïve (T24) cells through two-dimensional gel electrophoresis and LC-MASS. PGK1 was 1 of 25 differently overexpressed proteins (>1.5-fold change) in T24CDDPR cells compared with T24 cells [ 107 ]. Wang’s group claimed that, in addition to platinum-based compounds, shikonin can specifically bind to PKM2, but PKM1 does not.…”
Section: Various Effects Of Glycolytic Enzymes On Phenotypes Of Ucmentioning
confidence: 99%